PRODUKSI DAN NILAI NUTRIEN HIJAUAN KACANG TUNGGAK DAN RUMPUT SUDAN DALAM POLA TANAM TUMPANG SARI DI LAHAN KERING - Bernadete B. Koten; Redempta Wea; Agustinus Paga (Partner, 2008)
The aim of this research are to evaluate the production and nutritive value Cowpea and sudan grass forage on intercroping plant system. This research was designed by RCD with 5 treatment and replication ( 25 attempt unit). Treatment tried by are: P1: Monoculture sudan grass, P2: Monoculture cowpea, P3 Join with cowpea and Sudan grass in percentage population 25:75, P4:50:50 and P5:75:25.The result showed that intercroping cowpea and sudan grass effected ( P< 0,01) on dry matter production on sudan grass and cowpea there P3 and P4 are highest that 3,18 tons / ha and 3,04 tons / ha for sudan grass and on Cowpea 7,03 tons / ha and 6,35 tons / ha. Crude protein on sudan grass forage, P5 And P4 are highest that 10,50% and P4 10,25%. Best Rate crude fiber on P3 and P4. P1 And P3 crude fat highest that 1,00% and 0,89%, and ash highest at P1, P4 And P5 that 12,83%, 12,28% and 12,17%. For cowpea forage, the best Nutritive value are CP highest at P4 and P5 that 27,72% and 27,59%. Best rate CF at P5 and P4 that 21,06% and 20,89%. highest rate Crude fat at P2 and P3 that 2,05% and 1,69%. highest ash rate at P2 that 17,07%. Concluded the best proportion for join plant sudan grass and cowpea is 50 %: 50 %. Keywords: sudangrass, cowpea, forage, intercroping, crop https://ebiteua.com/anal-sex